BACE1 Inhibition Increases Susceptibility to Oxidative Stress by Promoting Mitochondrial Damage - Carolina Francelin; Sayak K. Mitter; Qingwen Qian; Sandeep Kumar Barodia; Colin Ip; Xiaoping Qi; Hongmei Gu; Judith Quigley; Matthew S. Goldberg; Maria B. Grant; Michael E. Boulton (MDPI AG, 2021)
BACE1 is a key enzyme facilitating the generation of neurotoxic β-amyloid (Aβ) peptide. However, given that BACE1 has multiple substrates we explored the importance of BACE1 in the maintenance of retinal pigment epithelial (RPE) cell homeostasis under oxidative stress. Inhibition of BACE1 reduced mitochondrial membrane potential, increased mitochondrial fragmentation, and increased cleaved caspase-3 expression in cells under oxidative stress. BACE1 inhibition also resulted in significantly lower levels of mitochondrial fusion proteins OPA1 and MFN1 suggesting a higher rate of mitochondrial fission while increasing the levels of mitophagic proteins Parkin and PINK1 and autophagosome numbers. In contrast, BACE2 had minimal effect on cellular response to oxidative stress. In summary, our results emphasize the importance of BACE1 in augmenting cellular defense against oxidative stress by protecting mitochondrial dynamics.